Analyzing Ohm's Law: Comparison of Current and Resistance in Series and Parallel Circuits - Imtiyaaza, Kuni Afrida; As’ari, Safira Aila; Cahyani, Khoirunnisa Aprilia; Nurbayana, Faradilla Sari; Zahro, Zurrotur Rofiqotin; Nagifea, Friscela Yona; Sudarti, Sudarti; Baihaqi, Habibah Khusna (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study is to analyze and compare the relationship between current and resistance in series and parallel circuits, and to verify the accuracy of Ohm's Law through experimental measurements and theoretical calculations. Methodology: This study uses a Pre-Experimental Design (One-Group Post-Test Only Design), involving 10 series and 10 parallel circuits with resistors of varying values. Measurements of current and resistance were taken using a digital multimeter and ohmmeter. Data collection occurred at three time points (start, 5 minutes, 10 minutes). The data was compared with theoretical values based on Ohm's Law. Main Findings: The experiment showed that in a series circuit, the current increased proportionally with the applied voltage, consistent with Ohm's Law. In parallel circuits, the current also increased with voltage, but at a higher rate compared to series circuits. The resistance measured in both circuit types was consistent with theoretical calculations, with minor percentage errors observed in both configurations. Novelty/Originality of this study: This study offers a fresh perspective by analyzing the application of Ohm’s Law in both series and parallel circuits, comparing real experimental data with theoretical calculations. It advances existing knowledge by providing a practical verification of theoretical concepts, enhancing understanding of current distribution and resistance effects in different circuit configurations, which can benefit students and professionals in electronics.